Uptake of nitrogen and production of kainic acid by laboratory culture of the red alga Digenea simplex. Issue 1 (25th September 2017) - Jiang, Shanshan; Kuwano, Kazuyoshi; Nishihara, Gregory N.; Urata, Chisato; Shimoda, Ryusuke; Takatani, Tomohiro; Arakawa, Osamu
SUMMARY: The red alga Digenea simplex was cultured with various culture media to clarify the nutritional conditions to produce kainic acid (KA). Unlike the domoic acid‐producing red alga Chondria armata, D. simplex was insensitive to excessive manganese, and grew best (mean growth rate approximately 800% for 25 days) in modified PES medium (mPES; seawater + nitrate, phosphate, iron, trace metals, vitamins, and 2‐[4‐(2‐hydroxyethyl)‐1‐piperazinyl]‐ ethanesulfonic acid) prepared with autoclaved seawater. Liquid chromatography‐mass spectrometry analysis of the algal extracts revealed that the KA content of the explants cultured with mPES or N·P·Fe medium (seawater + nitrate, phosphate, and iron) was somewhat higher than that of wild specimens (1748–2378 μg g −1 vs 1562 μg g −1 ). The 1 H‐nuclear magnetic resonance spectrum of the KA extracted and purified from pooled explants was indistinguishable from the previously reported KA spectrum. When D. simplex was cultured for 6 weeks with medium in which NaNO3 of mPES was replaced by Na 15 NO3, the ratio of 214 KA to total measured KA ( total KA = 213 KA + 214 KA) in the cultured explants (0.1 at the beginning of culture) gradually increased to 2.5, indicating that D. simplex produces KA in proportion to its growth under the condition in which sufficient nitrogen source is available.